Sustainable urban development: An examination of literature evolution on urban carrying capacity in the Chinese context. (20th December 2020) - Meng, Conghui; Du, Xiaoyun; Ren, Yitian; Shen, Liyin; Cheng, Guangyu; Wang, Jinhuan
Abstract: Research interests in urban carrying capacity (UCC) in the contemporary urbanizing China have been growing in recent years, which results in the development of a large body of related articles. This research examines the research evolution in the discipline of UCC in the Chinese context. It is considered important to understand this research evolution thus future research trend can be perceived. The study was conducted in the framework of sustainable urban development. The research evolution of UCC is captured and portrayed by introducing two novel parameters, namely, scaling attention (SA) and relative attention (RA). The bibliometric analysis approach is used to conduct the analysis. The data used for analysis are retrieved from two databases of China National Knowledge Infrastructure (CNKI) and Web of Science (WoS). The research findings suggest that: 1) the research works on UCC in the specificity of Chinese context have been increasing significantly in recent years across three sustainable development categories of social, economic and environmental carrying capacity; 2) the research attention on UCC was only contributed to the dimension of land carrying capacity in economic category in China before 1985, and the research works on the dimensions of medical service, education, culture, safety, employment in social category emerged latest since 2010; 3) the research within the category of environmental carrying capacity has been attracting increasingly more attention in recent years than that within social and economic categories. In particular, the dimensions of land, water and ecology in environmental category are highly attended in the survey period; 4) the overall highly attended UCC dimensions in literature include water carrying capacity, land carrying capacity, transportation carrying capacity and tourism carrying capacity. Highlights: Research evolution on urban carrying capacity (UCC) is investigated by bibliometric approach. Scaling attention (SA) and relative attention (RA) are developed to capture UCC research evolution. Environmental category has received highest research attention among the three-pillar of sustainable urban development. Research hotspots and future research agenda of UCC are delineated. Policy implications are drawn up towards enhancing UCC and urban sustainability.